A study of reading habits and interests among secondary school students in SMK Kuala Telemong,Hulu Terengganu, Terengganu / Siti Normala Muhamad - Muhamad, Siti Normala (2006)
The primary purpose of this investigation was to examine and gain an insight into the respondents' reactions towards reading habits, the use of library in SMK Kuala Telemong and to determine students' interests or preferences in reading. A set of questionnaire was used to gather the data which were carefully tabulated and analyzed. The research was conducted on 100 students in Form 3 and Form 5 at SMK Kuala Telemong (SMK Kuala Telemong) in Hulu Terengganu. The results indicated that 33.0% of the respondents read regularly outside school hours but their reading tended to be confined mainly to textbooks. With regards to non-textbook reading, there was the preference of reading non-fiction over fiction materials. Reading, therefore, is undertaken mainly for acquiring knowledge or for studying purposes. Recreational reading of fiction materials is mostly confined to reading the newspapers. The findings also showed that the 96.0% of the respondents preferred to read more in Bahasa Malayu than English. It is hoped that the outcomes of this study will be beneficial to the teachers in assisting their students to inculcate reading habits. Furthermore, it is hoped that the finding will lead to the development of suitable reading materials especially among students. This will go a long way in nurturing and fostering the reading habits and interests of the students. It is also hoped that this study will stimulate further in-depth studies which will help to improve the reading habits and interests in SMK Kuala Telemong particularly and Terengganu generally.